Institutional investors and post-ICO performance: an empirical analysis of investor returns in initial coin offerings (ICOs) - Fisch, Christian; Momtaz, Paul P. (Journal of Corporate Finance, 2020)
We examine the role of institutional investors in initial coin offerings (ICOs). Taking a financial investor's perspective, we assess the determinants of post-ICO performance via buy-and-hold abnormal returns (BHAR) in a sample of 565 ICO ventures. Conceptually, we argue that institutional investors' superior screening (selection effect) and coaching abilities (treatment effect) enable them to partly overcome the information asymmetry of the ICO context and extract informational rents from their ICO investments. We find that institutional investor backing is indeed associated with higher post-ICO performance. Disentangling selection and treatment effects econometrically, we find that both of these effects explain the positive impact institutional investors have on post-ICO performance. Overall, our results highlight the importance of institutional investors in the ICO context.